Pengaruh Kepemimpinan Kepala Desa Terhadap Perencanaan Pembangunan Desa Di Kecamatan Kao Utara Kabupaten Halmahera Utara. - Soputan, Chatrinne; Rares, Joyce; Tampi, Gustaf Budi (Sam Ratulangi University, 2015)
ABSTRACT: According to Law No. 32 Year 2004 on Regional Government , the Village is acommunity unit which has a limit of jurisdiction , authority to control and take care of the interests ofthe local community based task origins local customs that are recognized or established within thenational administration system and located in the District / City .Participatory rural development in order to be able to walk and reach the target effectively . Asin katakana by Nugroho (2003 ) that planning is an activity of the development process of the highestpriority , because it determines the direction of planning and development strategies .In the government regulation No. 6 of 2014 on the village , mentioned that the villagegovernment planning Rural Development in accordance with the authority with reference to theplanning district / city . Development plan prepared in a participatory village by village government inaccordance with its authority .Keywords : Effects of Leadership , Planning , Rural Development